MRI and the Critical Care Patient: Clinical, Operational, and Financial Challenges - Barbara McLean; Douglas Thompson (Critical Care Research and Practice)
Neuroimaging in conjunction with a neurologic examination has become a valuable resource for today’s intensive care unit (ICU) physicians. Imaging provides critical information during the assessment and ongoing neuromonitoring of patients for toxic-metabolic or structural injury of the brain. A patient’s condition can change rapidly, and interventions may require imaging. When making this determination, the benefit must be weighed against possible risks associated with intrahospital transport. The patient’s condition is assessed to decide if they are stable enough to leave the ICU for an extended period. Intrahospital transport risks include adverse events related to the physical nature of the transport, the change in the environment, or relocating equipment used to monitor the patient. Adverse events can be categorized as minor (e.g., clinical decompensation) or major (e.g., requiring immediate intervention) and may occur in preparation or during transport. Regardless of the type of event experienced, any intervention during transport impacts the patient and may lead to delayed treatment and disruption of critical care. This review summarizes the commentary on the current literature on the associated risks and provides insight into the costs as well as provider experiences. Approximately, one-third of patients who are transported from the ICU to an imaging suite may experience an adverse event. This creates an additional risk for extending a patient’s stay in the ICU. The delay in obtaining imaging can negatively impact the patient’s treatment plan and affect long-term outcomes as increased disability or mortality. Disruption of ICU therapy can decrease respiratory function after the patient returns from transport. Because of the complex care team needed for patient transport, the staff time alone can cost $200 or more. New technologies and advancements are needed to reduce patient risk and improve safety.